2014
DOI: 10.1177/0194599814541627a219
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Aspirin: A Systematic Review of Its Impact on Sensorineural Hearing Loss

Abstract: Objective-This systematic review evaluates the impact of aspirin on audiometric outcomes with respect to: (1) doses exceeding 325 mg daily, (2) doses of 325 mg daily or less, (3) studies applicable to the general populace, and (4) studies applicable to those with inflammatory conditions. It also assesses the impact of aspirin on (a) self-reported hearing loss, (b) noiseinduced audiometric changes, and (c) the adverse otological effects of aminoglycoside therapy.Data Sources-Computerized searches of MEDLINE, Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…1 For example, in the case reported here, the aspirin therapy was discontinued due to ototoxicity concerns, but a systematic review found the hearing loss associated with aspirin to be dose dependent only for doses exceeding 325 mg daily. 9 The authors of the review were not able to rule out lower-dose, longer-term aspirin therapy as a possible causative or contributing factor to hearing loss, but the risk of cardiovascular disease without aspirin is an important consideration in the decision-making process.…”
Section: Autoimmune Inner Ear Diseasementioning
confidence: 99%
“…1 For example, in the case reported here, the aspirin therapy was discontinued due to ototoxicity concerns, but a systematic review found the hearing loss associated with aspirin to be dose dependent only for doses exceeding 325 mg daily. 9 The authors of the review were not able to rule out lower-dose, longer-term aspirin therapy as a possible causative or contributing factor to hearing loss, but the risk of cardiovascular disease without aspirin is an important consideration in the decision-making process.…”
Section: Autoimmune Inner Ear Diseasementioning
confidence: 99%
“…The likewise old remedy aspirin is known to cause tinnitus and impaired hearing when taken in overdose. A systematic review involving 185,000 individuals extracted from 37 publications has recently been published with the main aim to evaluate the effect on audiometric measurements in different dose ranges . The authors found sensorineural hearing loss documented for daily doses from 4 to 10 g per day with a reported threshold shift of 15–112 dB.…”
Section: Other Audiological Responses: Comparison Between Quinine Andmentioning
confidence: 99%
“…3 However, studies show that administration of high doses Aspirin (325 mg) had an ototoxic effect leading to hearing loss. 4 On the other hand, studies have shown that co-administration of Aspirin with gentamicin, which is considered to be ototoxic, had a protective effect against hearing loss, 5 also animal studies have shown that NSAIDs in low doses can protect against cochlear injury due to noise and aging, but the effect on human is yet to be determined. 6 In our study, we aimed to find out if administration of low dose Aspirin (81 mg) had a protective impact against hearing loss due to aging.…”
Section: Introductionmentioning
confidence: 99%